Simultaneous Engineering and Knowledge Management in a Semiconductor Manufacturing Firm Using TQM - Rani, Seema; Reddy, Jayashankar; Poongavanam, S. (International Journal of Supply Chain Management, 2018)
For a long time, add up to quality administration, simultaneous designing and learning administration have won extensive consideration from modern specialists and the scholarly community. Be that as it may, few examinations have been directed on the impact of these three practices among Malaysian assembling firms. Subsequently, the target of this examination is to break down the impact of TQM, CE and KM on designing execution in a Malaysian semiconductor producing firm. For this investigation, overviews were utilized to get observational information on these three practices. The information was investigated utilizing different straight relapse examination. The discoveries demonstrated that TQM, CE and KM essentially impacts the companys building execution with the three indicators disclosing up to 53.9% of the fluctuation in designing execution. The discoveries of this examination are helpful to administrators, specialists and analysts as it gives bits of knowledge on particular zones that require sufficient thoughtfulness regarding guarantee compelling designing execution.